2022
DOI: 10.3389/fcimb.2022.833339
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite Triggers Reprogramming of the Oral Polymicrobial Metabolome by a Commensal Streptococcus

Abstract: Commensal streptococci regulate health and homeostasis within oral polymicrobial communities. Remarkably, high salivary nitrite concentrations have also been associated with improved health in the oral cavity. We previously demonstrated that nitrite assists hydrogen peroxide-producing oral commensal streptococci in regulating homeostasis via the generation of reactive nitrogen species (RNS), which have antimicrobial activity on oral pathogens. However, it is unknown how nitrite and commensal streptococci work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Although the mechanisms of such adhesions and coaggregations are not fully elucidated, it is believed that the extracellular polysaccharide (EPS) matrix of S. mutans has an important role in this process. , It is reported that glucans synthesized by Gtfs when incorporated into the tooth pellicle to provide enhanced binding sites for other microorganisms to form stable and persistent microcolonies, which provides mechanical stability to the EPS matrix. , Therefore, Gtf inhibition assays were performed to assess the ability of HA5 to inhibit Gtfs and glucan production using a reported procedure and the IC 50 value was calculated . Compound HA5 exhibited dose-dependent inhibition of glucan production by Gtfs with an IC 50 value of 10.56 μM (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanisms of such adhesions and coaggregations are not fully elucidated, it is believed that the extracellular polysaccharide (EPS) matrix of S. mutans has an important role in this process. , It is reported that glucans synthesized by Gtfs when incorporated into the tooth pellicle to provide enhanced binding sites for other microorganisms to form stable and persistent microcolonies, which provides mechanical stability to the EPS matrix. , Therefore, Gtf inhibition assays were performed to assess the ability of HA5 to inhibit Gtfs and glucan production using a reported procedure and the IC 50 value was calculated . Compound HA5 exhibited dose-dependent inhibition of glucan production by Gtfs with an IC 50 value of 10.56 μM (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Accompanying metabolomic analysis uncovered the secondary metabolite thioproline as a potential protective antioxidant produced S. parasanguinis (Huffines et al, 2022).…”
Section: According To Recently Reported Evidence Commensalmentioning
confidence: 99%
“…This along with the multicellular spreading behavior of the cross-kingdom biofilm is beneficial to S. mutans survival and biofilm development. The inhibitory effect is heightened by the presence of salivary nitrite (Huffines et al, 2022), which promotes the generation of reactive nitrogen species to which cariogenic species are sensitive.…”
Section: Candida Albicans and Oral Streptococcusmentioning
confidence: 99%
See 2 more Smart Citations